PENYELESAIAN KREDIT BERMASALAH MELALUI OFFSET JAMINAN DI BANK BUKOPIN CABANG BANDA ACEH - Dina Refina; Dahlan Dahlan; Sri Walny Rahayu (Jurnal Ilmu Hukum, 2016)
Abstract: The regulation of Indonesian Central Bank (known as Bank Indonesia or BI) No. 7/ 2/ Pbi/ Year 2005, Article 1 Point 15 has been applied as reference by the credit repayment in the form of offset guarantee delivered by PT. Bank Bukopin branch office of Banda Aceh with its credit loaner or debtor. This mentions “every collateral in any form of assets - that has been taken over and obtained by the bank - either through an auction or not from the debtor, is presumed as confiscatory item or bank’s asset (activa)”. The bank is authorized by its debtor to entitle his/her collateral either freely or not if he/she fails to comply his/her obligation. In the practice, however, there has been no clearly stated clause which guarantees debtor’s objection to entitle freely his collateral to the bank (in this regard Bank Bukopin) and to proceed it further by the credit repayment process. This has been referred as offset guarantee. Basically, to authorize the bank the selling of  collateral belong to a debtor is not a problem as long as the sale of an object or the sale price of the initial object is advantageous for both parties. This will be a problem if the sale of an object or sale price determined by the bank is usually below the market price, which disadvantages debitor’s interest. The offset guarantee can be employed in the repayment process only if the collaterals are in the form of fixed-properties, or located in the municipality, and/ or if main branch office of Bank Bukopin is available.Keywords: collateral, credit repayment, offset guarantee, selling authority.Abstrak: Peraturan Bank Central Indonesia (dikenal sebagai Bank Indonesia atau BI) No. 7/ 2/ Pbi/ Tahun 2005, Pasal 1 Angka 15 telah ditetapkan sebagai dasar dalam proses penyelesaian kredit dalam bentuk jaminan offset yang dikeluarkan oleh PT. Bank Bukopin Cabang Banda Aceh dengan peminjam kredit atau debitor.  Peraturan tersebut menyebutkan bahwa “setiap agunan dalam bentuk apapun - yang telah diambil alih dan didapatkan oleh  bank – baik melalui pelelangan ataupun tidak  dari debitor, dianggap sebagai bahan sitaan atau aset dari bank (aktiva)”. Bank diberikan kuasa oleh si debitor untuk menyerahkan agunannya baik secara sukarela atau tidak jika dia tidak dapat memenuhi kewajibannya.  Namun dalam praktiknya, belum ada klausul yang tercantum jelas yang menjamin keberatan debitor untuk menyerahkan agunannya secara sukarela kepada bank (dalam hal ini Bank Bukopin) dan kemudian memprosesnya secara lanjut dalam proses penyelesaian kredit. Hal ini disebut sebagai garansi offset. Pada dasarnya, memberikan kuasa kepada bank untuk menjual agunan milik debitor tidak menjadi persoalan asalkan penjualan suatu obyek atau harga jual obyek tanggungan menguntungkan kedua belah pihak. Ini akan menjadi persoalan apabila penjualan suatu objek atau harga jual yang ditentukan oleh bank biasanya dibawah harga pasar, yang merugikan kepentingan debitor. Jaminan offset ini hanya dapat dilakukan dalam proses pengembalian hanya jika agunan merupakan benda tidak bergerak, atau berada di daerah kotamadya dan/atau terdapat kantor cabang utama Bank Bukopin.Kata kunci: agunan, pembayaran kredit, jaminan offset, kuasa menjual.